HUBUNGAN ANTARA INTERNAL LOCUS OF CONTROL DAN PENGALAMAN PRAKTIK KERJA INDUSTRI DENGAN KEMATANGAN KARIER PADA SISWA PROGRAM STUDI KEAHLIAN TEKNIK KOMPUTER DAN INFORMATIKA - Mita Puspita dewi; Dessy Seri Wahyuni; I Made Gede Sunarya (Jurnal Pendidikan Teknologi dan Kejuruan, 2014)
This study aimed to determine the relationship between internal locus of controltoward career maturity, the relationship between practice industrial work experience toward career maturity, it also the relationship between internal locus of control and practiceindustrial work experience toward career maturity, that is student career maturity SkillsProgram in Computer Enginering and Information Technology at SMK in Buleleng regency academic year 2013/2014.This type of research is a correlation study that is expost-facto which consists of two independent variables that is internal locus of control (X1) and practice industrial workexperience (X2), it also one dependent variable that is career maturity (Y). The population in this study were 531 people and the sample were 175 respondents. Data for X1, X2, and Y wer